Experience capitalization: Fighting rural poverty in India, Nepal and Bhutan - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
This report comprises 12 case stories produced through the Experience Capitalization project implemented by CTA in different parts of the world. Poor and marginal communities are the primary subject of all other project interventions covered, including strengthening current occupations like goat rearing, experimenting with alternatives like poultry, or using unused or degraded resources to create livelihood opportunities. Almost all stories are dotted with innovations in institutional development, community participation, delivery of services, capacity building, financing, entrepreneurship and much more. Women and their empowerment is the subject of the two stories from Nepal and explore how access to finance and business skills can help them out of poverty.